2015
DOI: 10.1149/06801.1403ecst
|View full text |Cite
|
Sign up to set email alerts
|

Li/Na Modified Ni-SDC Anode for Methane-Fueled Solid Oxide Fuel Cells

Abstract: A facile chemical lithium/sodium insertion method has been developed to prepare Li/Na modified-NiO composites (Li/Na-NiO). The single cells were fabricated with a Li/Na modified NiO-Ce 0.8 Sm 0.2 O 1.9 (SDC) composite anode screened on a 300 µm La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O 3-δ (LSGM) electrolyte and a composite cathode consisting of Sr 0.95 Ce 0.05 CoO 3-δ and SDC (30 wt%). The cells with Li/Na modified Ni-SDC anode material deliver much higher open circuit voltages (OCV) than the cell with pure Ni-SDC anode.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…There has been considerable interest in the direct operation of solid oxide fuel cells (SOFCs) with hydrocarbon fuels [1][2][3][4][5][6][7][8][9][10][11]. Unlike an internal reforming, directly electrochemical oxidation of hydrocarbon in SOFCs do not need to introduce a substantial amount of H2O, CO2 or O2, which greatly simplifies the system and reduces the cost [12][13]. The most commonly used nickel/yttria-stabilized zirconia (Ni/YSZ) anodes have showed excellent performance in H2 fuel; however, there is serious carbon deposition when hydrocarbon fuels are used [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…There has been considerable interest in the direct operation of solid oxide fuel cells (SOFCs) with hydrocarbon fuels [1][2][3][4][5][6][7][8][9][10][11]. Unlike an internal reforming, directly electrochemical oxidation of hydrocarbon in SOFCs do not need to introduce a substantial amount of H2O, CO2 or O2, which greatly simplifies the system and reduces the cost [12][13]. The most commonly used nickel/yttria-stabilized zirconia (Ni/YSZ) anodes have showed excellent performance in H2 fuel; however, there is serious carbon deposition when hydrocarbon fuels are used [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they showed better long-term stability in 70 h, which was attributed to the unique ability of the alkaline metals to absorb H 2 O and CO 2 under the SOFC operating conditions. 141…”
Section: The Development Of Hydrocarbon-fueled Anodesmentioning
confidence: 99%
“…Moreover, they showed better long-term stability in 70 h, which was attributed to the unique ability of the alkaline metals to absorb H 2 O and CO 2 under the SOFC operating conditions. 141 Takeguchi et al found that the addition of CaO with strong basicity to Ni-YSZ cermet modified the metal Ni to a slightly cationic state, which was effective in inhibiting carbon deposition without reducing the reforming activity. 24 Asamoto et al also drew a comparable conclusion, namely, that the addition of CaO to the Ni-SDC anode slightly reduced the MPD; however, it enhanced the stability of the SOFC performance and inhibited carbon deposition on the anode.…”
Section: Bimetallic-cermet Materialsmentioning
confidence: 99%
“…Liu et al studied the doping of alkali metals (Li or Na) with NiO powder to formulate anode material with enhanced features [59]. Both Li-Ni-SDC and Na-Ni-SDC anodes have been found to increase the capability of adsorbing water vapour and CO 2 under cell operating conditions, enhancing coking tolerance and prevent the deactivation of the anode.…”
Section: Anode Surface Decoration or Incorporation Of Additional Mate...mentioning
confidence: 99%